From the gates of Troy to the trenches of the Western front: the representation of war in The iliad and in novels of the Great War - Vieira, Luiz Gustavo Leitão (Em Tese, 2008)
This paper aims at comparing war narratives. Whereas in the Iliad we are provided with powerful, necessarily named warriors, in the Great War novels All Quiet on the Western Front, Paths of Glory, and Company K, we encounter powerless soldiers. The principal feature these narratives share is war’s inherent unpredictability.